Evaluation of Hepatoprotective Activity of Tribulus terrestris in D-Galactosamine- and Paracetamol-Induced Hepatotoxicity in the Rat Model - Gupta, Ramji; Nitya Sharma; Mujahid, Mohd Hasan; Ahmed, Sumeer (Food and Drug Safety, 2026)
In traditional Indian and Chinese medicine, Tribulus terrestris has been frequently used to treat liver problems. The aim of this study was to look at the protective effect on the liver of the airborne (leaves, stems, fruits, flowers) leaves, stems, fruits, and flowers of the plant against hepatotoxicity caused by D-galactosamine (D-Gal) and paracetamol. To measure the antioxidant capacity of T. terrestris, we conducted a DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging assay. In the trials involving solvent fractions, the extraction of the ethanol extract exhibited the highest amount of free radical scavengers; thus, it was chosen for the continued tests on the protective nature of the liver. The ethanol extract was subjected to acute oral toxicity tests (OECD Test Guideline 425 up-and-down) to establish 200 mg/kg body weight and 400 mg/kg body weight as the doses to evaluate the protective effect. Comparisons of the protective effects of the ethanol extract of T. terrestris and Silymarin 100 mg/kg body weight were made based on their respective effectiveness in reducing the increased levels of the serum enzymes, Serum Glutamate Pyruvate Transaminase (SGPT), Serum Glutamate Oxaloacetate Transaminase (SGOT), alkaline phosphatase, total cholesterol, total bilirubin, and direct bilirubin caused by D Gal. Additionally, the level of protection against poison was tested by evaluating the condition and histology of the liver. In both models of D-galactosamine (D-GalN)- and paracetamol (PCM)-induced liver injury, administration of the ethanolic extract of T. terrestris at a dose of DBH (400 mg/kg body weight (bw)) produced significantly greater hepatoprotection than either D-GalN or PCM (+) silymarin (100 mg/kg) (p = 0.07). This finding indicates that the ethanolic extract of T. terrestris has considerable protection against D-galactosamine-induced hepatic injury by acting as an antioxidant and stabilizing membranes.